Personnel System Application Design on CV. Intan Bakery Prabumulih City - Adriano Dwi Sinjery; Fajriyah; Andi Christian (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Information technology is a technology that is generally used to assist humans in creating, changing, storing, communicating and disseminating information. By implementing a staffing system application in an organization or company, it can make it easier for management to plan, supervise, direct, and delegate work to all departments that have a command or coordination relationship with them. As well as increasing the efficiency and effectiveness of data that is presented accurately and on time. One of them is the implementation of the staffing system application. In employee processing, information is needed to make it easier to carry out employee performance. One of the important bases or references in establishing a policy in the field of personnel is employee data, in the form of individual data for each employee complete with their history. Personnel administration activities will affect the state of individual employee data and as a whole. The existence of computer devices is not too much help, because the data is stored and managed by each executor and not in a unified platform. Management or processing is the science and art of managing, controlling, communicating and utilizing all resources. This staffing system application is made using a website.